Nutrient Uptake by Rice Plant Inoculated with Microaerophilic Rhizobacteria Isolated from Selected Rice Soils - Neo, Sye Peng (2002)
The major problem of rice cultivation is low efficiency of N fertilizer and increasing production costs due to the rising price of N fertilizer. Nitrogen fertilizer inputs constitute a high proportion of the price of production. The biological nitrogen fixation technology by inoculating plants with diazotrophic rhizobacteria is an alternative that would subsequently reduces cereal production cost. The study consisted of two experiments. Experiment I was the isolation of microaerophilic rhizobacterial strains from rice soil. Experiment II was a glasshouse experiment to study the effect of selected microaerophilic rhizobacteria on rice nutrient uptake under glasshouse condition. From the isolation procedures, 62 rhizobacterial isolates were collected from different rice soils. Twenty-six or 41.93% isolates showed positive results in nitrogen-free media test. Among the positive strains, six isolates (designated as E 1 8, E23, E38, E40, E44 and E47) with comparatively the highest c.f.u. were studied under the microscope and applied as inoculant in subsequent glasshouse experiment. In the glasshouse experiment, a factorial experiment comprising 6 strains X 5 concentrations of nitrogen input with 5 replications were set up giving a total of 1 50 pots. Rice plants inoculated with rhizobacteria E44 showed the tendency to increase nitrogen content, rhizobacteria E38 tends to increase plant phosphorus content, and rhizobacteria E40 inoculation tends to increase dry weight of rice plants. Meanwhile, inoculation of rhizobacteria E40 showed the tendency to increase shoot magnesium content while rhizobacteria E23 tends to increase root magnesium content. There was no obvious result that shows either potassium and calcium uptake of rice plant were promoted by inoculation with the isolated rhizobacteria. In conclusion, rhizospheres of rice cultivation areas were found to have high populations of microaerophilic rhizobacteria that have the potential to be diazotrophs. The selected rhizobacterial strains respectively showed the trend to promote plant growth (in term of total dry weight) and nutrient (nitrogen, phosphorus, potassium, calcium and magnesium) uptake of rice plants. Therefore, they could have the potential to be applied as biofertilizer or bioenhancer.